(untitled) (Desenvolvimento em Questão, 2025)
This study explores the relationship between Araguaia River within the state of Tocantins, Brazilian Amazon, and Blue Bioeconomy using a methodology grounded in related studies, secondary data, the Locational Quotient (LQ), and ANOVA statistics. This procedure allowed a comparison analysis with the southern Tocantins River, which has a quite distinct profile from Araguaia. Results indicate that the Araguaia-Blue Bioeconomy link is rooted in landscape exploration for tourism, particularly in the municipalities of Araguacema and Caseara, generating employment and income, as well as in the preservation of local knowledge exemplified by traditional fishing within communities. The integration of these activities should foster regional development, provided that recurrent territorial conflicts are resolved, which originated from past neglect and misguided decisions by authorities.